The Judas ear : poems - Journey, Anna, 1980- (Louisiana State University Press, 2022)
"The poems in Anna Journey's new collection, The Judas Ear, resurrect a host of vanished people and places, often through marvelous Ovidian metamorphoses that are as natural in the gritty tableaux of Richmond, Virginia, as in the luminous shape-shifting vistas of folktale or myth. A restaurant server donates her eggs to a fertility agency for rent money and morphs into the golden goose, a pair of art-school roommates communicate through a private language based on Renaissance artist Arcimboldo's invertible paintings that change from portrait to still life, and a vintage pink couch sourced from a meningitis clinic transforms from an object of domestic comfort to a viral threat. Journey's music is lush and visceral, her humor warm and sly, and her sensibility metes out tenderness and grotesquerie in equal parts. Taking its title from the ear-shaped mushroom named for a biblical betrayer, The Judas Ear offers poems that can shift suddenly from wit to pathos, from seductiveness to danger, with a generosity of vision that is at once wise and revelatory"-- Provided by publisher.
Keywords: Poetry.; Poetry as Topic; Poésie.; poetry.; Poetry; Electronic books.